The Role of the West Provincial Environment and Forestry Agency in Sustainable Environmental Management and Community Empowerment - Nurmalasari Nurmalasari; Sripe Wafiq Aziza; Subriati Subriati; Nurfadilah Nurfadillah; Nurlia Nurlia (JURNAL ILMIAH DETUBUYA, 2025)
This study aims to examine the role of the West Nusa Tenggara Provincial Environment and Forestry Agency (DLHK) in implementing sustainable environmental management and community empowerment efforts. The research was conducted using a qualitative approach to gain an in-depth understanding of the institutional role, program implementation, and various challenges faced by the DLHK in maintaining a balance between environmental conservation and socio-economic development. Data collection was carried out through in-depth interviews with DLHK NTB officials and direct observation of the organizational structure, infrastructure, and implementation of environmental programs. In addition, local government support through policies, regulations, and cross-sector coordination strengthens program sustainability, while the use of environmental service technology promotes transparency and public participation. This study confirms that sustainable environmental management in NTB Province requires a holistic approach that integrates ecological, social, and economic aspects with active community involvement.